Self Esteem dengan Perilaku Merokok Siswa - Herriyanto Kono; M. K. P Abdi Keraf; Marleni P. Panis (Journal of Health and Behavioral Science, 2020)
This research is a correlation analysis with quantitative approach. The study aims to discribe the assosiation of level relationship between self-esteem and smoking behavior of students in SMK Negeri 2 Soe. Samples were male students of SMK Negeri 2 Soe numbering 70 students. Data was collected by using a scale of self-esteem and smoking behavior questionnaire and then use computer programs for data analysis. Hypothesis testing using Pearson produck moment correlation test to see the correlation between the two variables. The results show the value of the correlation coefficient of -0.333 with a significance value (p) of 0.005 which means Ha accepted that there is a relationship between self-esteem and smoking behavior of students in State Vocational High School 2 Soe.